MEDIA WEIGHTED JACKET DAN WEIGHTED BELT UNTUK KEKUATAN TUNGKAI ATLET POLO AIR : STUDI LITERATUR - Pratiwi, Ayudya Suidarwanty; Mulyana, Boyke; Sidik, Dikdik Zafar (UNIVERSITAS NEGERI MAKASSAR, 2020)
Water polo is a full body contact sport. It is the combination of swimming, rugby, soccer, and basketball. The basic skills to be mastered in water polo are swimming, water trapping, and ball controlling using hands while floating in the water supported by egg-beater foot movement, where the leg endurance is the main point to perfect this technique. Athletes need leg endurance to float and swim during the game. This study is a literature review aimed at analyzing water polo athletes’ training using weighted jacket and weighted belt in water on their strength and leg endurance. The data were collected from research results published in national and international journals from 1991 to 2019. Therefore, the data were analyzed using content analysis. The review result revealed that the strategy to combine weighted jacket and weighted belt to train water polo athletes’ leg endurance was more effective. Weighted belts were worn around the athlete's waist, and heavy objects that were generally used for scuba diving were placed on belts. On the other hand, weighted jackets must be placed directly below the waist and the weight is suspended between the legs. The jacket with soft, durable, and waterproof material can be adjusted to the athlete's body size. The use of weighted jacket and weighted belt training media in water polo affected the strength and leg endurance of water polo athletes directly.